Undiagnosed Hypothyroidism: Culprit for Fenofibrate Induced Rhabdomyolysis - Shahi, Ravi; Simkhada, Rabindra; Koirala, Parash; Neupane, Keshab Raj (Nepalese Heart Journal, 2024)
Fenofibrate induced rhabdomyolysis is not very common event. We present a case of muscle pain and generalized weakness following administration of fenofibrate for 10 days in undiagnosed hypothyroidism. Patient gradually improved after stopping the drug. As per our knowledge, this is probably the first case report of fenofibrate induced rhabdomyolysis from Nepal.